The Effect of Institutional Ownership and Auditor Independence on Tax Avoidance - Taufik Hidayat (International Journal of Economics (IJEC), 2022)
Taxes are one of the biggest sources of APBN revenue. This biggest income must continue to be properly increased so that the country's growth rate can run well. Taxpayer non-compliance is usually done in various ways such as tax evasion. Tax evasion is an effort to reduce the tax burden legally without violating tax regulations by taxpayers by trying to reduce the amount of tax owed by looking for loopholes in tax regulations. This research is a quantitative research with an associative approach. The data analysis tool uses the SPSS version 22 program. The locations taken in this study are listed non-financial sector companies listed on the IDX with the research period 2016 to 2018. Institutional ownership has no negative effect on tax evasion. The results of this study support previous research by Dewi and Jati (2014) who found that institutional ownership has no effect on tax control. However, it is different from the research results of Alviyani (2016) which proves that institutional ownership has a negative effect on tax avoidance . Auditor independence has no negative effect on tax evasion. This research is in line with research by Tandean (2016) which states that auditor independence has no effect on tax evasion, but this research is not in line with research by Kartiko & Martani (2013) which states that in the long term after auditor rotation, the quality of accounting earnings is getting better and indirectly directly affect the reduction of tax avoidance actions.